2019
DOI: 10.7717/peerj.7026
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Fagus crenata (subgenus Fagus) and comparison with F. engleriana (subgenus Engleriana)

Abstract: This study reports the whole chloroplast genome of Fagus crenata (subgenus Fagus), a foundation tree species of Japanese temperate forests. The genome has a total of 158,227 bp containing 111 genes, including 76 protein-coding genes, 31 tRNA genes and 4 ribosomal RNA genes. Comparison with the only other published Fagus chloroplast genome, F. engeleriana (subgenus Engleriana) shows that the genomes are relatively conserved with no inversions or rearrangements observed while the proportion of nucleotide sites d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Consistent with previous reported values for Fagus plastomes (35.5% for F . crenata [ 32 ]; 37.0% for F . engleriana [ 34 ]; and 37.1% for F .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with previous reported values for Fagus plastomes (35.5% for F . crenata [ 32 ]; 37.0% for F . engleriana [ 34 ]; and 37.1% for F .…”
Section: Resultsmentioning
confidence: 99%
“…crenata (subgenus Fagus ) and F . engleriana (subgenus Engleriana ) [ 32 ]. The study found substantially lower pairwise nucleotide differences (p-distances) between the two species of Fagus than between those of its sister genus Quercus (0.0018 vs. 0.0042) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations